Asymmetric Total Syntheses of Kopsane Alkaloids via a PtCl2‐Catalyzed Intramolecular [3+2] Cycloaddition. (25th May 2020) - Jia, Xuelei; Lei, Honghui; Han, Feipeng; Zhang, Tao; Chen, Ying; Xu, Zhengshuang; Nakliang, Pratanphorn; Choi, Sun; Guo, Yian; Ye, Tao
Abstract: A concise and asymmetric total synthesis of five kopsane alkaloids that share a unique heptacyclic caged ring system was accomplished. The key transformation in the sequence involved a remarkable PtCl2 ‐catalyzed intramolecular [3+2] cycloaddition, which allowed for the rapid assembly of pentacyclic carbon skeletons bearing 2, 3‐quaternary functionalized indoline. Expeditious construction of diverse indoline scaffolds with excellent control of diastereoselectivity demonstrated the broad scope and versatility of this key transformation. Abstract : Asymmetric total synthesis of five kopsane alkaloids containing a heptacyclic caged ring system was accomplished. The total synthesis hinges on a PtCl2 ‐catalyzed intramolecular [3+2] cycloaddition, which promotes assembly of pentacyclic carbon skeletons bearing 2, 3‐quaternaryfunctionalized indoline scaffolds with excellent control of diastereoselectivity.